সেই সে কাল : সরদার ফজলুল করিম - ফজলুল করিম, সরদার, ১৯২৫- (নাজমা জেসমিন চৌধুরী স্মারক বক্তৃতা ;)
Autobiographical reminiscences of a leftist leader, university teacher, and writer from Bangladesh about his involvement in political activities before the independence of his country in 1971.